A practical model for computation with matrix groups. (May 2015) - Bäärnhielm, Henrik; Holt, Derek; Leedham-Green, C.R.; O'Brien, E.A.
Abstract: We describe an algorithm to compute a composition tree for a matrix group defined over a finite field, and show how to use the associated structure to carry out computations with such groups; these include finding composition and chief series, the soluble radical, and Sylow subgroups.